Practical training report: Hotel Equatorial, Kuala Lumpur / Satar Yusof - Yusof, Satar (1982)
Towering 17 storeys high, Hotel Equatorial presents a magnificient panoramic view of the city.Set against a beautiful tropical skyline amidst luxuriant greenery within easy reach ofall parts of the city. Three hundred;' )luxuriously comfortable rooms and suites. elegantly furnished with air conditioning , private bath, music, phone and wall to wall carpeting so designed to pamper any guest.The hotel incorporates a 24-hour:Coffee Shop/and 3 specialty restaurants serving Japanese, Swiss, and Chinese cuisine respectively,2 lounges and a spacious lobby. For meeting and Conventions, the hotel boasts of the Ballroom, Mawar, Raya and Cempaka with facilities from a minimum of 5 up to600 complete with audio -visualreqipment. •It also incorporates a swimming pool and shopping arcade, laundry and valet, 24-hour room service and telephone and telex services.And for safety measures, the hotel is equipped throughout with fire springklers. lt is a complete businessman's and family retreat.